2017
DOI: 10.4103/0974-8490.199777
|View full text |Cite
|
Sign up to set email alerts
|

Chronic intake of green propolis negatively affecting the rat testis

Abstract: Background:Human and animal evidence suggests that environmental toxicants may have an adverse impact on male reproductive health, reducing the population's reproductive output. Owing to the renewed attraction for natural products, some of them constitute effective alternatives to mitigate these effects. Propolis is a candidate for this use because of its intrinsic properties. In many situations, it improved the testicular damage and alleviated the toxic effects induced by environmental contaminant exposure.Ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…CAPE has been reported to reduce apoptosis ( 14 , 17 , 20 , 47 ). Conversely, Severi-Aguiar et al ( 58 ) noticed that 10 mg of propolis/kg/day induced Cx43 upregulation and caused morphological damage to germ cells, Sertoli cells, and Leydig cells. They observed that apoptotic cells were present in the germinal epithelium of the testes in a dose-dependent manner in their studies.…”
Section: Discussionmentioning
confidence: 99%
“…CAPE has been reported to reduce apoptosis ( 14 , 17 , 20 , 47 ). Conversely, Severi-Aguiar et al ( 58 ) noticed that 10 mg of propolis/kg/day induced Cx43 upregulation and caused morphological damage to germ cells, Sertoli cells, and Leydig cells. They observed that apoptotic cells were present in the germinal epithelium of the testes in a dose-dependent manner in their studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are different opinions about effect on reproduction system of phenolic compounds. Severi‐Aguiar et al () informed that chronic dosses of propolis on the male rats may cause reproductive disruption which can be linked to phenolic compounds present in propolis.…”
Section: Discussionmentioning
confidence: 99%